Escape depth of secondary electrons from electron-irradiated polymers - Hessel, Roberto [UNESP] (1992)
Measurements on polymers (Teflon FEP and Mylar) have shown that the secondary electron emission from uncharged surfaces exceeds that from surfaces containing a positive surface charge. The reduced emission of charged surfaces is due to recombination between electrons undergoing emission and trapped holes within the charged layer. During the experiments the surface of the material was kept at a negative potential to assure that all secondary electrons reaching the surface from within the material are actually emitted. An analysis of the results yielded the maximum escape depth of the secondary electrons, and showed that the ratio of the maximum escape depth of the secondaries from Mylar to the maximum escape depth from Teflon is almost the same as the ratio of the corresponding second crossover energies of this polymers.